Cumulative Effect of Crumb Rubber and Steel Fiber on the Flexural Toughness of Concrete - Abu Bakar, Badorul Hisham; Noaman, Ahmed Tareq; Md. Aki, Hazizan (Engineering, Technology and Applied Science Research, 2017)
Concrete properties, such as toughness and ductility, are enhanced to resist different impacts or blast loads. Rubberized concrete, which could be considered a green material, is produced from recycled waste tires grinded into different crumb rubber particle sizes and mixed with concrete. In this study, the behavior of rubberized steel fiber-reinforced concrete is investigated. Flexural performance of concrete beams (400